Infant-Directed Speech From a Multidimensional Perspective: The Interplay of Infant Birth Status, Maternal Parenting Stress, and Dyadic Co-regulation on Infant-Directed Speech Linguistic and Pragmatic Features - Spinelli, Maria; Lionetti, Francesca; Garito, Maria Concetta; Shah, Prachi E.; Logrieco, Maria Grazia; Ponzetti, Silvia; Cicioni, Paola; Di Valerio, Susanna; Fasolo, Mirco (Frontiers in Psychology, 2022)
Infant-directed speech (IDS), the particular form of spontaneous language observed in interactions between parents and their infants, is a crucial aspect of the mother-infant interaction and an index of the attunement of maternal linguistic input to her infant communicative abilities and needs during dyadic interactions. The present study aimed to explore linguistic and pragmatic features of IDS during mother-infant interactions at 3-months of infant age. The effects of infant (birth status: preterm vs full-term birth), maternal (perceived parenting stress) and dyadic (dyadic co-regulation) factors on IDS was explored. Results evidenced few differences between the groups on IDS linguistic characteristics. Moreover, observing the interaction of birth status and dyadic co-regulation, full-term mothers vary their IDS pragmatic features according to the quality of co-regulation while preterm mothers did not. Parenting stress was associated to specific linguistic IDS features independently from the birth status. Findings are discussed underling implications for the study of preterm dyads interactions and the importance to consider the interplay of several factors in affecting the quality of IDS.